2015
DOI: 10.1007/s00417-015-2936-z
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical effects of clear lens extraction by phacoemulsification versus trabeculectomy on anterior chamber drainage angle in primary angle-closure glaucoma (PACG) patients

Abstract: Compared to trabeculectomy, clear lens extraction resulted in a significant reduction in synechial angle closure, and an increase in anterior chamber angle width and anterior chamber depth in PACG eyes without cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 19 publications
0
24
1
Order By: Relevance
“…The crystalline lens is larger than an IOL in anterior-posterior thickness and volume. After cataract surgery, the irislens diaphragm moves backward and increases the anterior chamber volume and expands the iridocorneal angle (8). Cataract surgery relieves the load on the anterior chamber with the removal of the swollen lens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystalline lens is larger than an IOL in anterior-posterior thickness and volume. After cataract surgery, the irislens diaphragm moves backward and increases the anterior chamber volume and expands the iridocorneal angle (8). Cataract surgery relieves the load on the anterior chamber with the removal of the swollen lens.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is a subjective technique and influenced by the experience of the examiner (7). There are many studies in the literature that demonstrate the effect of phacoemulsification on narrow-angle glaucoma (8,9). The aim of this study was to evaluate these changes in open-angle glaucoma using anterior segment optical coherence tomography (AS-OCT).…”
Section: Introductionmentioning
confidence: 99%
“…Measurement methods varied in different studies including: Haag-Streit pachymetry (Haag-Streit AG, Koeniz, Switzerland),[1316] A-scan (Cinescan; Quantel Medical, Clermont-Ferrand, France),[911] ultrasound biomicroscopy (UBM Vumax II, Sonomed Inc., NY, USA),[1719] and IOL master (Carl Zeiss Meditec AG, Jena, Germany). [18] The studies which evaluated patients in immediate postoperative periods showed that the ACD was the shallowest on days 2-4, and then deepened gradually to reach 87-91% of its preoperative values on day 14.…”
Section: Resultsmentioning
confidence: 99%
“…Asian patients have significantly lower adherence to glaucoma eyedrops than Caucasian patients, hence being medication‐free is particularly advantageous and may be associated with a better quality of life. Previous studies have shown that phacoemulsification alone is effective in lowering the IOP in angle closure eyes by widening the angle . Reduction of medication, especially in PACG patients, is also important in terms of cost‐effectiveness of treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Lens extraction results in IOP reduction between 2 and 12 mmHg . The IOP‐lowering effect is greater in PACG than in POAG, through widening the angles and reducing the extent of total peripheral anterior synechiae . Previous randomized controlled trials (RCTs) have shown that combined phacoemulsification and trabeculectomy reduces the amount of glaucoma medications more than phacoemulsification alone in angle closure eyes, at the expense of a higher rate of complications …”
Section: Introductionmentioning
confidence: 99%